Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.jconrel.2011.08.032
|View full text |Cite
|
Sign up to set email alerts
|

A poly(ethylene glycol)-based surfactant for formulation of drug-loaded mucus penetrating particles

Abstract: Mucosal surfaces are protected by a highly viscoelastic and adhesive mucus layer that traps most foreign particles, including conventional drug and gene carriers. Trapped particles are eliminated on the order of seconds to hours by mucus clearance mechanisms, precluding sustained and targeted drug and nucleic acid delivery to mucosal tissues. We have previously shown that polymeric coatings that minimize adhesive interactions with mucus constituents lead to particles that rapidly penetrate human mucus secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 32 publications
2
61
0
Order By: Relevance
“…This optimization increased by 3.7-and 11.7-fold Ptx bioavailability compared with standard LNCs and Ptx commercial formulation, respectively. It was demonstrated that the coating of particles with PEG increased diffusion through the mucus layer [48] if PEG had an optimal molecular weight [49] and if coating was dense enough [50]. These muco-penetrating particles used to promote oral absorption of drug, improve efficiently the bioavailability of Ptx [51].…”
Section: Discussionmentioning
confidence: 99%
“…This optimization increased by 3.7-and 11.7-fold Ptx bioavailability compared with standard LNCs and Ptx commercial formulation, respectively. It was demonstrated that the coating of particles with PEG increased diffusion through the mucus layer [48] if PEG had an optimal molecular weight [49] and if coating was dense enough [50]. These muco-penetrating particles used to promote oral absorption of drug, improve efficiently the bioavailability of Ptx [51].…”
Section: Discussionmentioning
confidence: 99%
“…Added to this, mucus provides a substantial barrier to the diffusion of large, charged and lipophilic entities, which can dramatically reduce diffusion rates [87][88][89]. Indeed, these issues have resulted in increasing interest in the development of muco-inert carrier systems in the form of mucus-penetrating particles that avoid interaction with mucus and thus experience a lower diffusion barrier [84,[90][91][92][93].…”
Section: Relevance For Mucoadhesionmentioning
confidence: 99%
“…A novel surfactant molecule for particle formulation composed of Vitamin E conjugated to 5 kDa poly(ethylene glycol) (VP5k) was used instead of Vitamin E conjugated to 1kDa PEG (Vitamin E-TPGS). VP5k-coated PLGA NPs rapidly penetrated human cervicovaginal mucus, whereas PLGA NPs coated with PVA or Vitamin TPGS were trapped [45].…”
Section: Vitamin Ementioning
confidence: 99%